Association between ionised calcium and severity of postpartum haemorrhage: a retrospective cohort study. (May 2021) - Epstein, Danny; Solomon, Neta; Korytny, Alexander; Marcusohn, Erez; Freund, Yaacov; Avrahami, Ron; Neuberger, Ami; Raz, Aeyal; Miller, Asaf
Abstract: Background: Postpartum haemorrhage (PPH) is often complicated by impaired coagulation. We aimed to determine whether the level of ionised calcium (Ca 2+ ), an essential coagulation co-factor, at diagnosis of PPH is associated with bleeding severity. Methods: This was a retrospective cohort study of women diagnosed with PPH during vaginal delivery between January 2009 and April 2020. Ca 2+ levels at PPH diagnosis were compared between women who progressed to severe PPH (primary outcome) and those with less severe bleeding. Severe PPH was defined by transfusion of ≥2 blood units, arterial embolisation or emergency surgery, admission to ICU, or death. Associations between other variables (e.g. fibrinogen concentration) and bleeding severity were also assessed. Results: For 436 patients included in the analysis, hypocalcaemia was more common among patients with severe PPH (51.5% vs 10.6%, P <0.001). In a multivariable logistic regression model, Ca 2+ and fibrinogen were the only parameters independently associated with PPH severity with odds ratios of 1.14 for each 10 mg dl −1 decrease in fibrinogen (95% confidence interval [CI], 1.05–1.24; P =0.002) and 1.97 for each 0.1 mmol L −1 decrease in Ca 2+ (95% CI, 1.25–3.1; P =0.003). The performance of Ca 2+ or fibrinogen was not significantly different (area under the curve [AUC]=0.79 [95% CI, 0.75–0.83] vs AUC=0.86 [95% CI, 0.82–0.9]; P =0.09). The addition of Ca 2+ to fibrinogen improved the model, leading to AUC of 0.9 (95% CI, 0.86–0.93), P =0.03. Conclusions: Ca 2+ level at the time of diagnosis of PPH was associated with risk of severe bleeding. Ca 2+ monitoring may facilitate identification and treatment of high-risk patients.